Exploring Students' Perceptions of 'Speakia' App for Speaking Lessons - Irmayani Irmayani; Annis Rahmawati; Syifa Khuriyatuz Zahro (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
This study aims to explore students’ perceptions of "Speakia" as a medium for enhancing English speaking skills. A descriptive qualitative research design was employed to analyze the responses collected through a structured questionnaire combined with qualitative interviews and a literature review from related studies. The instrument comprised 15 questions using a 5-point Likert Scale, accompanied by an open-ended section for additional comments. The questions addressed students’ positive impressions of Speakia, specific benefits, levels of motivation and comfort, encountered difficulties, and suggestions for improvement. A purposive sampling technique was utilized to thoughtfully select participants who could provide valuable insights related to the research objectives. The study involved 29 participants (13 males and 16 females) from an Islamic primary school in Lamongan, Indonesia. Findings indicated that the majority of students responded positively to the use of Speakia, reporting increased confidence and comfort in speaking English. However, less than 10% of the participants experienced difficulties, particularly in comprehending the audio pronunciations provided by Speakia, largely due to unfamiliarity with native speaker accents. The study concludes that the selection of appropriate learning media plays a critical role in enhancing the quality of language learning, influencing student engagement, and ultimately, the effectiveness of instructional delivery. Speakia is positively received as an online learning medium, demonstrating its efficacy in fostering both student engagement and proficiency in English language acquisition. The findings offer valuable data-driven insights for educators, policymakers, and developers, enabling them to refine or expand the use of such technological tools